A PHYTOSOCIOLOGICAL STUDY OF WOODY VEGETATION Those NEAR IBADAN, NIGERIA - Kamo, Koichi; Kiatvuttinon, Bopit; Viriyabuncha, Chingchai; Kuerkool, Pin (วารสารวนศาสตร์ไทย, 2022)
The structure and floristic composition of both woody and herbaceous vegetation in the Botanical Garden of the University of Ibadan campus in Nigeria were studied. The area experiences tropical climate having an annual rainfall of 1,740.3 mm and the average mean daily temperature of 25° to 29° C. All the species observed during the point-centered quarter analysis (121 species) and also the others (52 species) were recorded. The vegetation was dominated by phanerophytes. The families represented by the greatest number of species were Leguminosae, Euphorbiaceae, Bignoniaceae, Sterculiaceae and Apocynaceae. The herbaceous vegetation was studied by laying down quadrats, and consisted of 59 species. Based on the Importance Value Index, the woody vegetation was named as Delonix-Elaeis-Lagerstroemia Community while the herbaceous vegetation was Tridax-Synedrella-Pennisetum Community. The association index calculated for the species having the highest frequency with certain other species revealed that Calopogonium mucunoides and Sida acuta were highly associated. Seasonality effect was not marked in the prevailing vegetation